Chronic Non-Healing Ulcers Associated with Atopic Inflammation: A Case Report - Yang X; Wang H; Song Z; Chen Q (Dove Medical Press, 2022)
Xianjie Yang, Huan Wang, Zhiqiang Song, Qiquan Chen Department of Dermatology, Southwest Hospital, Army Medical University, Chongqing, People's Republic of ChinaCorrespondence: Qiquan Chen, Department of Dermatology, Southwest Hospital, Army Medical University, No. 28 Gaotanyan Steet, Shapingba District, Chongqing, People's Republic of China, Tel +86-15683418212, Email chenqq0548@163.comAbstract: Chronic non-healing ulcers are the undesirable outcome of delayed wound healing influenced by many factors. It can be seen in patients with diabetes, autoimmune conditions and multiple primary skin conditions. But chronic non-healing ulcers secondary to atopic inflammation are rarely reported in the literature. In this study, we reported a case with wounds caused by the wrong tattoo and surgery, activation of atopic inflammation caused delayed wound healing and the formation of chronic non-healing ulcers. The patient's atopic inflammation was relieved and stabilized with oral cyclosporine and topical application of halometasone cream and subsequently 0.1% tacrolimus cream, and then the chronic non-healing ulcers healed well, without recurrence at a follow-up visit 3 months later.Keywords: chronic non-healing ulcers, wound healing, type 2 inflammation, atopic inflammation, eosinophils, cyclosporine